Knowledge Level of Farmers and the Importance of Coffee Seedling Attributes and Accessibilities in Bandung Regency, West Java, Indonesia - Dina Fithriyyah; Eliana Wulandari; Tuhpawana P. Sendjaja (Indonesian Coffee and Cocoa Research Institute, 2020)
Bandung Regency is one of the main Arabica coffee plant development centers in West Java, especially in Pangalengan District. The problem of Arabicacoffee farming is that the seedlings used not from recommended seed gardens, which may affect coffee productivity in the future. There are several factors thatinfluence farmers in the selection of coffee seedlings, including the knowledge of farmers on the attributes of coffee seedlings, and the importance of the attributes. The purpose of this study were 1) analyzing farmers’perception on the importance of different coffee seedlings attributes; 2) analyzing farmers’ knowledge of the seedlings attributes in each coffee variety; 3) analyzing the level of suitability and gap of the attributes of Arabica coffee seedling and the position of various categories of attributes and seedling accessibility in the concept of priority. The research method used quantitative approach from 77 coffee farmers. The data was analysed using descriptive analysis, Importance Performance Analysis and Cartesian diagrams. The results show that in general all the coffee attributes and seedlings accessibility evaluated had a positive score and very important for farmers. Furthermore, the farmers’ knowledge on the attributes and seedlings accessibility was variaed. Farmers have good knowledge on seedlings size, productive age, productivity, fertilizer use efficiency, seedling price, and ease of obtaining seedling attributes. There is an unsuitability and gap between the important and knowledge level of farmers about coffee attributes and seedlings accessibility.